30 rock. Season 7, the final season [videorecording (DVD)] - Fey, Tina, 1970-; Baldwin, Alec, 1958-; Morgan, Tracy, 1968-; Krakowski, Jane; McBrayer, Jack, 1973-; Adsit, Scott, 1965-; Friedlander, Judah (Universal Studios Home Entertainment, 2013)
The complete seventh and final season of the award-winning comedy. As Jack schemes to take control of KableTown or sink the whole company trying, Liz strives to balance her uncharacteristically blissful personal life with the constant chaos of her career. Even with Kenneth Parcell, life-long NBC devotee, around to tend to TGS' lovable misfit stars Tracy Jordan and Jenna Maroney, mayhem ensues with a season of thirteen episodes.